What are the Strengths and Limitations of Queer Theory for Understanding the Categories of Gender, Sexuality and Bodies - Li, Fangbin (International Journal of Social Sciences and Public Administration, 2024)
This article explores the development of Queer Theory and its impact on gender, sexual behavior, and bodily classifications. The theory is believed to have originated from an article by Teresa de Lauretis in 1991, initially aimed at unifying the LGBTQ+ community in response to the backlash against sexual minority rights in the latter half of the 20th century. Over time, the term "queer" has evolved to encompass individuals and communities diverging from mainstream sexual behaviors, including lesbian, gay, bisexual, transgender, non-binary, and gender non-conforming individuals, as well as heterosexual individuals engaging with Queer Theory. It challenges the binary gender structure and norms of traditional LGBTQ+ cultures, emphasizing the performative nature of gender and resisting categorization.